Fish community structure in high water temperature around Bontang Industrial Estate, East Kalimantan, Indonesia - IWAN SUYATNA; A. SYAFEI SIDIK; ISMAIL FAHMY ALMADI; SAMSUL RIZAL; KOMSANAH SUKARTI (Biodiversitas Journal of Biological Diversity, 2016)
Suyatna I, Sidik AS, Almadi FA, Rizal S, Sukarti K. 2016. Fish community structure in high water temperature around Bontang Industrial Estate, East Kalimantan, Indonesia. Biodiversitas 17: 558-564. We have conducted studies on fish community and their physical and chemical properties of coastal waters in the work area of the industrial estate from 2012 to 2014. At least four industries are known to use the coastal waters in cooling their processing equipments, the hot wastewater is then discharged back into the coastal environment. The current study reports the result of a survey undertaken around the work area of PT Blackbear Resources Indonesia. The result showed that high water temperature and tidal fluctuation are affecting the fish community in the area. By sampling results, during HWL of the spring tide at the maximum of water temperature of 35,9 oC, fish were the most populated and found 5999 ind. or 72,4% of the total number of 8291 fish. During LWL of the same tide type fish were observed 1931 ind oC, this ambient showed that the fish population drastically change in number and the environment became undesirable.